Platinum Group Elements (PGE) Geochemistry and Mineralogy of Low Economic Potential (Rh-Pt-Pd)-Rich Chromitites from Ophiolite Complexes - Zaccarini, Federica (MDPI, 2022)
This contribution provides an overview of platinum group elements (PGE) distribution and mineralogy in ophiolitic chromitites, which are unusually enriched in the low melting-point Rh, Pt and Pd (PPGE) compared with most chromite deposits associated with ophiolites, which are dominated by the refractory Os, Ir and Ru (IPGE). The PPGE-rich chromitites examined in this paper have a PPGE/IPGE ratio equal to or higher than 1 and represent about 7 of the ophiolitic chromitite population. These chromitites occur in the mantle unit, in the mantle-transition zone (MTZ), as well as in the supra-Moho cumulate sequence of ophiolite complexes. The age of their host ophiolites varies from Proterozoic to Eocene and, based on their composition, the chromitites can be classified into Cr-rich and Al-rich categories. Mineralogical assemblages observed in this investigation suggest that the PPGE enrichment was achieved in the magmatic stage thanks to the formation of an immiscible sulfide liquid segregating during or immediately after chromite precipitation. The sulfide liquid collected the available chalcophile PPGE that precipitated as specific phases together with Ni-Cu-Fe sulfides in the host chromitite and the silicate matrix. After their magmatic precipitation, the PPGM and associated sulfides were altered during low-temperature serpentinization and hydrothermal processes. Therefore, the original high-temperature assemblage underwent desulfurization, generating awaruite and alloys characterized by variable Pt-Pd-Rh-Cu-Ni-Fe assemblages. The occurrence of secondary PPGM containing Sb, As, Bi, Te, Sn, Hg, Pb and Au suggests that these elements might have been originally present in the differentiating magmatic sulfide liquid or, alternatively, they were introduced by an external source transported by hydrothermal and hydrous fluids during the low-temperature evolution of the host ophiolite. Although the PGE content may be as high as 81,867 ppb, as was found in one sample from Shetland chromite deposits, the ophiolitic chromitites are not presently considered as a potential resource because of the following circumstances: (1) enrichment of PPGE in podiform chromitites is a local event that occurs randomly in ophiolite sequences, (2) ore deposits are small and characterized by uneven distribution and high discontinuity, (3) physical characters of the mineralization only allow poor recovery of the precious metals mainly due to the minute grain size, and (4) for these reasons, the PPGE reserves in ophiolitic chromitites cannot compete, at the moment, with those in chromite deposits of the Bushveld type that will supply world demands for centuries using current mining techniques. © 2022 by the authors.